2016
DOI: 10.1021/acsami.6b11391
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Impeding AgNPs Target Skin Carcinoma by Inducing Mitochondrial Membrane Depolarization Mediated through ROS Production

Abstract: Reactive oxygen species (ROS) are a double-edged sword that possesses both beneficial and harmful effects. Although basic research on skin cancer prevention has undergone a huge transformation, cases of recurrence with higher rates of drug resistance are some of its drawbacks. Therefore, targeting mitochondria by ROS overproduction provides an alternate approach for anticancer therapy. In the present study, green-synthesized silver nanoparticles (AgNPs) were explored for triggering the ROS production in A431 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Alteration in mitochondrial membrane permeability leads to the formation of mitochondrial permeability transition pores (MPTP) which facilitates unchecked inflow of solutes and free radicals inside the cell. This uncontrolled inflow causes increase of osmotic pressure inside the inner mitochondrial complex and thus finally leads to the overall collapse of the mitochondrial membrane which is considered as the initial step for the activation of the intrinsic cell death pathways 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in mitochondrial membrane permeability leads to the formation of mitochondrial permeability transition pores (MPTP) which facilitates unchecked inflow of solutes and free radicals inside the cell. This uncontrolled inflow causes increase of osmotic pressure inside the inner mitochondrial complex and thus finally leads to the overall collapse of the mitochondrial membrane which is considered as the initial step for the activation of the intrinsic cell death pathways 64 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS generation damages the biofilm’s integrity and architecture by breaking the biofilm biomatrix and its constituent biomolecules. The biofilm matrix contains eDNA, protein and polysaccharides which are easily damaged by ROS action [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive use may lead to side effects such as gastrointestinal irritation, jaw osteonecrosis, hypocalcemia, and inflammatory eye disorders [20,21]. Otto et al indicated that bisphosphonates exhibited a pH-dependent cellular toxicity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The cells that migrated into the scratched area were imaged at 0 and 24 h and the migrated dis-tance was quantified. The migration ratio (%) was calculated as fol-lows: Migration ratio (%) = (original wound width-remaining wound width)/original wound width × 100 [20]. …”
Section: Methodsmentioning
confidence: 99%